Reflexivity as situated problem-solving: a pragmatist alternative to general theory - Holmwood, John (Società editrice il Mulino, 2014)
Recent developments in sociological theory have addressed the linkage between structure and agency via a conception of reflexivity and the agent’s internal conversation as a means of understanding the (variable) contribution that the self and its powers contribute to social outcomes. In this paper, I present a sociological realism utilising the approach of American pragmatism (Dewey and Mead) to argue for a different way of conceptualising reflexivity, namely as an occasioned feature of interaction. On this view, reflexivity arises in relation to problems in interaction and is oriented to their resolution. It is argued that the self has a social structure and that reflexivity inheres in interactions and not in different types of individual self-identity. The paper discusses general issues of reflexivity in terms of conceptions of sociology’s “dialogic.” Archer’s relation to actors whose behaviours are under scrutiny, before going on to discuss Margaret Archer’s typology of the “inner dialogues” of actors and its use to understand social mobility.